1989
DOI: 10.1210/jcem-69-4-891
|View full text |Cite
|
Sign up to set email alerts
|

Thyroid-Stimulating Activity in Sera of Normal Pregnant Women

Abstract: To evaluate the effect of a thyroid stimulator on thyroid function in the sera of normal pregnant women, we measured thyroid-stimulating activity (TSA) using a highly sensitive bioassay based on cAMP accumulation in cultured rat FRTL-5 thyroid cells. Serum was pretreated with 10% polyethylene glycol (PEG), and the supernatant (PEG-pretreated serum) was then used in the following studies. FRTL-5 cells were preincubated in 5H medium and incubated for 2 h with PEG pretreated serum, and cAMP was measured. All 11 p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
37
0

Year Published

1990
1990
2011
2011

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 67 publications
(40 citation statements)
references
References 26 publications
3
37
0
Order By: Relevance
“…The origin of the increased maternal thyroid function is almost certainly stimulation of the TSH receptor by human chorionic gonadotrophin (hCG) (Guillame et al 1985, Yoshikawa et al 1989, Glinoer et al 1990, Ballabio et al 1991. As the fetal thyroid is active only after 14 weeks gestation,it is suggested that the increased maternal thyroid activity ensures that normal neuronal development occurs in the fetus (Shepard 1975).…”
Section: Introductionmentioning
confidence: 99%
“…The origin of the increased maternal thyroid function is almost certainly stimulation of the TSH receptor by human chorionic gonadotrophin (hCG) (Guillame et al 1985, Yoshikawa et al 1989, Glinoer et al 1990, Ballabio et al 1991. As the fetal thyroid is active only after 14 weeks gestation,it is suggested that the increased maternal thyroid activity ensures that normal neuronal development occurs in the fetus (Shepard 1975).…”
Section: Introductionmentioning
confidence: 99%
“…In all 9 normal pregnant women in the first trimester, TGA was within the normal range However, in two patients with hydatidiform mole, TGA was positive. We previously found thyroid stimulating activity determined by cAMP accumulation in the sera of almost all normal pregnant women (Yoshikawa et al, 1989a). The reason why TGA could be detected only in some patients with hydatidiform mole may be Lineweaver-Burk plots of dose response curves of TSH-(the upper two panels) and hCG-(the lower two panels) induced [3H] Tdr incorporation in the presence of normal IgG or blocking IgGs from patients with primary hypothyroidism (patients 5 and 10 listed in Table 1: patient 5 is shown in the left two panels and patients 10 in the right).…”
Section: Discussionmentioning
confidence: 99%
“…The cloned rat thyroid cell line ERTL-5, established from cells of rat thyroid adenoma by Ambesi-Impiombato et al (1980) was cultured as previously described (Yoshikawa et al, 1989b Serum pretreatment with PEG Serum was pretreated with PEG by the method previously described (Yoshikawa et al, 1989a). Briefly, serum was dialyzed against the Hanks' Balanced Salt Solution, incubated for 1h at 4 C with 10% PEG, centrifuged at 10,000 pretreated serum) was used for the TGA assay.…”
Section: Cell Culturementioning
confidence: 99%
See 2 more Smart Citations